Controllable hierarchical micro/nano patterns on biomaterial surfaces fabricated by ultrasonic nanocrystalline surface modification. (5th January 2018) - Liang, Yuan; Qin, Haifeng; Mehra, Nitin; Zhu, Jiahua; Yang, Zhengnan; Doll, Gary L.; Ye, Chang; Dong, Yalin
Abstract: In this work, we have shown that Ultrasonic Nanocrystal Surface Modification (UNSM) cannot only improve the mechanical properties of Ti-based biomaterials but also produce surface texture with hierarchical micro/nanoscale patterns due to its high controllability. After UNSM-treatment the surface texture of Ti-based biomaterial consists of a major microscale structure with widths ranging from 4 μm to 200 μm, and an embedded nanoscale structure with widths as small as 120 nm. With a customized cylinder tip, the average surface roughness ( Ra ) can be reduced to 0.03 μm, comparable to the superfinishing surface. The embedded nanoscale structure originates from the formation of the pile-up, which is determined by the elastic-plastic property of materials. Such hierarchical patterns enable new functions for the treated surface. It is demonstrated that light dispersion and the alteration of wettability can be achieved by controlling surface patterns using UNSM. The capacity of improving mechanical properties, biocompatibility, and hydrophobicity simultaneously, in conjunction with its low-cost and easy-to-operate features, makes it a promising surface engineering technique for biomaterial treatment. Graphical abstract: Highlights: Improved biocompatibility, which has been revealed in literature. A diffraction grating, a new optical property Modulate the wettability of the treated surface